2017
DOI: 10.1016/j.taap.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the heart's electrical properties by the anticonvulsant drug retigabine

Abstract: Retigabine, currently used as antiepileptic drug, has a wide range of potential medical uses. Administration of the drug in patients can lead to QT interval prolongation in the electrocardiogram and to cardiac arrhythmias in rare cases. This suggests that the drug may perturb the electrical properties of the heart, and the underlying mechanisms were investigated here. Effects of retigabine on currents through human cardiac ion channels, heterologously expressed in tsA-201 cells, were studied in whole-cell patc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(105 reference statements)
2
3
0
Order By: Relevance
“… Tykocki et al (2019) also suggested that retigabine may cause partial inhibition of the L-type Ca V channels in mouse DSM cells, consistent with prior findings ( Mani et al, 2013 ; Rubi et al, 2017 ). At 10 μM, retigabine weakly attenuated the mouse DSM inward voltage-gated Ca V current by ∼25% (from 8 to 6 pA/pF, evoked by the voltage step from −60 to +20 mV), while 60 mM KCl induced tonic contraction (primarily mediated via L-type Ca V channel activation) by ∼20% ( Tykocki et al, 2019 ).…”
Section: K V 7 Channel Functional Studies On Dsm Csupporting
confidence: 82%
See 2 more Smart Citations
“… Tykocki et al (2019) also suggested that retigabine may cause partial inhibition of the L-type Ca V channels in mouse DSM cells, consistent with prior findings ( Mani et al, 2013 ; Rubi et al, 2017 ). At 10 μM, retigabine weakly attenuated the mouse DSM inward voltage-gated Ca V current by ∼25% (from 8 to 6 pA/pF, evoked by the voltage step from −60 to +20 mV), while 60 mM KCl induced tonic contraction (primarily mediated via L-type Ca V channel activation) by ∼20% ( Tykocki et al, 2019 ).…”
Section: K V 7 Channel Functional Studies On Dsm Csupporting
confidence: 82%
“…Hence, future studies should address what may have been methodological issues and confirm the functional presence of K V 7 channels in mouse DSM cells using more precise patch-clamp protocols for recording native K V 7 channel currents. Tykocki et al (2019) also suggested that retigabine may cause partial inhibition of the L-type Ca V channels in mouse DSM cells, consistent with prior findings (Mani et al, 2013;Rubi et al, 2017). At 10 µM, retigabine weakly attenuated the mouse DSM inward voltage-gated Ca V current by ∼25% (from 8 to 6 pA/pF, evoked by the voltage step from −60 to +20 mV), while 60 mM KCl induced tonic contraction (primarily mediated via L-type Ca V channel activation) by ∼20% (Tykocki et al, 2019).…”
Section: Expression Of K V 7 Channel Subtypes In Dsm Whole-tissue Andsupporting
confidence: 80%
See 1 more Smart Citation
“…The only AED with a novel mechanism of action is an FDA approved retigabine (or ezogabine) in 2011 that activates the voltage-gated Kv7/KCNQ/M-channels for the treatment of partial epilepsy (Weisenberg and Wong, 2011). Nevertheless, the antiepileptic drug retigabine was recently withdrawn from the market due to its metabolites causing side effects such as vision change and discoloration of the skin (Rubi et al, 2017). 6 Kv7/KCNQ/M-channels are a subfamily of voltage-gated K + channels with five members, Kv7.1-7.5 (Gutman et al, 2005;Brown and Passmore, 2009a;Greene and Hoshi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…RTG can also activate all subtypes of the Kv7 family such as Kv7.2, Kv7.3, Kv7.4, Kv7.5, and Kv7.2/Kv7.3 channels, except Kv7.1, which is slightly inhibited by RTG (22). However, RTG renders adverse effects, including blue skin discoloration, retinal pigment abnormalities, and even cardiac arrhythmias (23)(24)(25), suggesting that a more specific Kv7 subtype activator is required for better efficacy and less toxicity.…”
mentioning
confidence: 99%